Bacterial nanowires: conductive as silicon, soft as polymer - Leung, J.M.; Wanger, G.; Guo, Q.; Gorby, Y.; Southam, G.; Ming Laue, G.; Yang, J.
It was recently discovered that Shewanella oneidensis MR-1, a dissimilatory metal-reducing bacterium, can grow electrically conductive extracellular appendages. Such bacterial nanowires, as they are termed, function as electron-transfer conduits to far-field electron acceptors or among neighbouring cells. A recent advance in the field was the characterization of bacterial nanowires' resistivity along their length, which is on the order of 1 U cm. This finding has motivated the exploration of their potential use in biofuel cells, bionanoelectronics and other bionanodevices. Along with conductivity measurements, it is also important to characterize the nature of these nanowires and their mechanical properties. In this work, we have confirmed the nature of these nanowires is protein. In addition, we have investigated the elasticity of bacterial nanowires using two independent atomic force microscopy techniques: (i)real-time elastic modulus mapping by AFM HarmoniX using T-shaped cantilevers with an offset tip and (ii)conventional AFM nanoindentation by force-distance curve fitting based on Hertz model. Results from both techniques demonstrated that the Young's modulus of bacterial nanowires is on the order of 1 GPa. This work inspires us with new applications of bacterial nanowires: with electrical conductivity comparable to that of moderately doped inorganic semiconductors and elasticity similar to polymeric materials, bacterial nanowires can function as electron-transfer conduits for biofuel cells and building blocks for bionanoelectronics and flexible nanoelectronics.